Toward a model for a-Si modules performance behavior under real outdoor operating conditions. (June 2015) - Polverini, Davide; Kenny, Robert; Huld, Thomas; Tzamalis, Georgios
Highlights: Extended seasonal measurements on 6 different a-Si modules (single, double and triple junction). Indoor controlled conditioning (light soaking and thermal annealing) on all the modules. Modeling of the behavior of each module by quantitatively assessing the irradiance and temperature contributions. Prediction of the module's performance beyond the measurement range via the proposed model. Abstract: Since the first research studies in the 1970s, the metastable behavior of amorphous silicon thin film photovoltaic modules has yet to be fully understood. In this paper a quantitative model for the performance of thin film amorphous and micromorph modules is presented. The first part of the experimental study consists of periodic indoor measurements of I – V characteristics on a set of six modules (single, double and triple junction), during a one year period of outdoor exposure. In the second part, light soaking and thermal annealing cycles were performed indoors on the same modules. The goal of the present research is to assess how the performance of a module is affected by the operating conditions, mainly temperature and irradiance, both of which contribute to a seasonal variation in its performance. For this purpose, a quantitative model is developed that takes into account both of these two contributions; the results show a good agreement between experimental and theoretical data. Further developments and model improvements are proposed and discussed.